Promethean Rebellion in Ray Bradbury’s "Fahrenheit 451": The Protagonist’s Quest - Feneja, Fernanda Luísa (Amaltea. Journal of Myth Criticism, 2012)
The article aims to reflect on the role of the myth in science fiction narrative, namely on the specific forms it may take in utopian/dystopian fiction, such as Fahrenheit 451 (1953) by Ray Bradbury. The personal development of the main character, Guy Montag, constitutes the focus of this analysis, by which we aim to shed some light on the relation between the meaning of the novel and the Promethean features he evinces in the context of a dystropian novel. The symbolic power of fire and of books is also of core relevance to this study, not only because the highlight the hero’s inheritance of the Promethean myth, but also because the provide a deeper insight into exegetic possibilities of dystopsian fiction